2006
DOI: 10.1095/biolreprod.105.049130
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RND Proteins in Human Myometrium1

Abstract: RHO GTPases are key regulators of the actin cytoskeleton and stress fiber formation. In the human uterus, activated RHOA forms a complex with RHO-associated protein kinase (ROCK) which inhibits myosin light chain phosphatase (PPP1R12A), causing a calcium-independent increase in myosin light chain phosphorylation and tension (Ca2+ sensitization). Recently discovered small GTP binding RND proteins can inhibit RHOA and ROCK interaction to reduce calcium sensitization. Very little is known about the expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 47 publications
(76 reference statements)
1
24
0
Order By: Relevance
“…Rnd2 and Rnd3 are also up-regulated in the human myometrium during pregnancy [26], but whether this is due to estradiol is not known. On the other hand, estradiol reduces Rnd3 expression in prostatic stromal cells [27].…”
Section: Rnd Expression Is Regulated By Diverse Stimuli Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rnd2 and Rnd3 are also up-regulated in the human myometrium during pregnancy [26], but whether this is due to estradiol is not known. On the other hand, estradiol reduces Rnd3 expression in prostatic stromal cells [27].…”
Section: Rnd Expression Is Regulated By Diverse Stimuli Transcriptionmentioning
confidence: 99%
“…[24]. In addition, Rnd1 and Rnd3 decrease myometrial smooth muscle cell contractility, and this is proposed to be important to prevent contraction of the myometrium until term in pregnancy [26,41]. A separate function for Rnd3 in muscle development is provided by the observation that it controls myoblast fusion in vitro [42].…”
Section: Rnd1 and Rnd3 Decrease Actomyosin Contractility And Regulatementioning
confidence: 99%
“…RND proteins are members of the Rho family which lack intrinsic GTPase activity and inhibit the RhoA-ROCK pathway either by binding to ROCK and preventing it from phosphorylating downstream targets [11] or by increasing Rho-GTPase activity via p190 Rho-GAP (Rho GTPaseactivating protein) [12]. We have demonstrated a pregnancyrelated up-regulation of RND2 and RND3 in human myometrium [13]. The up-regulation of myometrial RND protein expression is likely to be linked to inhibition of RhoA-ROCK signalling, and may increase MYLP activity that enhances uterine relaxation during pregnancy (see below).…”
Section: Involvement Of Rho-rock (Rho-associated Kinase) Signalling Imentioning
confidence: 81%
“…Myometrial MYPT1 protein levels are twofold higher in mice at day 13 of pregnancy than in nonpregnant animals (21,131). This contrasts with invariant human myometrial levels of MYPT1 between nonpregnant and full-term nonlaboring myometrium (120). This probably represents species differences; however, increases in MYPT1 levels earlier in human pregnancy might be masked by a return to nonpregnant levels at full term.…”
Section: )mentioning
confidence: 85%
“…In rats, ROCK1/2 mRNA was increased at full term or during labor (167,230,231); in mice, ROCK1/2 protein was increased during gestation (201). In humans, increased myometrial ROCK1/2 during pregnancy was reported (146); however, subsequent studies showed that myometrial ROCK1/2 mRNA and protein remained unchanged during human pregnancy and labor (65,120,123,200). Human myometrial ROCK1/2 activity during pregnancy has not been measured.…”
Section: Role Of Pp1 In Smooth Muscle Contractilitymentioning
confidence: 99%